2019
DOI: 10.1080/14739879.2019.1570349
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to brokering between research and care by senior clinical-scientists in general practice and elderly care medicine

Abstract: Background: Clinician-scientists (CSs) are physicians who work in daily care and have an academic role in research or education. They may act as knowledge brokers and help to connect research and clinical practice. There is no data available on CSs' brokering activities and the perceived barriers and facilitators to optimising their role in general practice (GP) and elderly care medicine (EM). Aim: To identify the brokering activities of CSs in these fields and the barriers and facilitators they come across wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Organizational support (access to resources, administrative, technical, and nancial support) can positively in uence the initiation and sustainability of the KBs role within an organization [31,74,81,[84][85][86]96]. Indeed, our ndings suggest that several forms of organizational support can impact the success of KBs roles.…”
Section: Organizational Levelmentioning
confidence: 71%
“…Organizational support (access to resources, administrative, technical, and nancial support) can positively in uence the initiation and sustainability of the KBs role within an organization [31,74,81,[84][85][86]96]. Indeed, our ndings suggest that several forms of organizational support can impact the success of KBs roles.…”
Section: Organizational Levelmentioning
confidence: 71%
“…Previous research indicated that dedicating nancial support for research activities can facilitate brokering activities. [40] In part, additional nancial support for KBs may be possible by encouraging collaborations between KBs and researchers in order to take advantage of funded research investigating brokering activities. [40] However, it is important for research projects to consider early on the sustainability of the KBs role for organisations to plan as needed to maintain the KBs role in the longterm.…”
Section: Discussionmentioning
confidence: 99%
“…[14,[32][33][34][35][36][37][38] Professionals who act as intermediaries in facilitating knowledge exchange between researchers and clinicians are referred to as human agents, [39] change agents [20] or opinion leaders, [11] while the most commonly used term in literature is brokers or knowledge brokers. [40] Knowledge brokers (KBs) are de ned as one of the human forces which bring people together to build relationships, identify practice needs, and share ideas to improve job productivity. [41] A recent systematic review reported that knowledge brokers can increase practitioners' adoption of evidencebased guidelines by 2.76 times (95% CI, 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 participants were interviewed in their (clinical or research) workplace; three participants were interviewed at their homes between June and August 2017. During the interviews, additional data were collected as this research is part of a larger research project (Bartelink et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%